Görünür ışık haberleşmesinde mesafe ve güce bağlı kanal modeli deneysel doğrulaması - Kısacık, Rıfat; Efe, Barış Can; Pusane, Ali Emre; Uysal, Murat; Baykaş, Tunçer; Dündar, Günhan; Yalçınkaya, Arda Deniz (IEEE-Inst Electrical Electronics Engineering Inc, 2019)
Bu bildiride, görünür ışık haberleşme sisteminde direkt görüş hattı için kanal modellemesi problemi ele alınmıştır. Sunulan kanal modelinde LED ve fotodiyot arasında filtre veya mercek gibi herhangi bir optik komponent bulunmamaktadır. Sonrasında, sözü edilen kanal modelinin benzetimi için uygun bir deney düzeneği kurulmuştur. Kurulan deney düzeneğinde LED ve fotodiyot karşılıklı olarak konumlandırılmıştır. LED ve fotodiyot arasındaki mesafe değiştirilerek fotodiyota ulaşan optik gücündeğişimi ölçülmüştür. Yapılan ölçüm kanal modeli ile karşılaştırılmıştır. Kanal modeli ile ilgili düzenekte yapılan ölçümsonuçlarının örtüştüğü gösterilmiştir. Daha sonra, alıcı çıkışındaki işaret gürültü oranı mesafeye bağlı olarak ölçülmüştür. Yapılan ölçümlerde kullanılan LED’ler için işaret-gürültü oranı 20 cm mesafeden sonra 15 dB seviyesinin altına inmiştir ve aradaki mesafe 50 cm olduğunda çıkıştaki sinyal seviyesi gürültü ile aynı düzeye erişmiştir.

In this work, a channel model for line-of-sight (LOS) in visible light communication is elaborated. In the proposed channel model, there is no optical component, such as filter or lens, between the transmitting LED and the receiving photodiode. Later, a suitable setup is built for emulation of the mentioned channel model. In the setup, the LED and the photodiode are located in a line-of-sight orientation. The change of the optical power on the photodiode is measured by varying the distance between the LED and photodiode. The measurement result is compared with the channel model. The channel model is in good agreement with the measurement results. Following that, the signal-to-noise ratio (SNR) at the output of the receiver, as a function of the distance, is measured. Measurement results indicate that the SNR value remains below 15 dB after exceeding a distance of 20 cm for the specific LED-Photodiode pair used in the experiment. The optical signal on photodiode drops to the noise level when the distance exceeds 50 cm.
Distance and power based experimental verification of channel model in visible light communication
27th Signal Processing and Communications Applications Conference, SIU 2019 April 2019, Article number 8806280 27th Signal Processing and Communications Applications Conference, SIU 2019; Sivas; Turkey; 24 April 2019 through 26 April 2019; Category numberCFP19559-ART; Code 151073
Keywords: Görünür Işık Haberleşmesi; Kanal Modellemesi; Sinyal Gürültü Oranı Ölçümü; Visible Light Communication; Channel Modeling; Signal-To-Noise Ratio Measurement